2014
DOI: 10.1002/app.40828
|View full text |Cite
|
Sign up to set email alerts
|

High dielectric constant polyimide derived from 5,5′‐bis[(4‐amino) phenoxy]‐2,2′‐bipyrimidine

Abstract: Polyimides (PIs) are highly desirable materials due to their excellent physical, chemical properties, and widespread applications. In this article, a new PI containing bipyrimidine units was prepared from a newly synthesized 5,5′‐bis[(4‐amino) phenoxy]‐2,2′‐bipyrimidine and 3‚3′‚4‚4′‐biphenyltetracarboxylic dianhydride via a two‐step method. The as‐synthesized PI not only showed high thermal stability and excellent mechanical properties, but also possessed high dielectric constant (7.1, 100 Hz) and low dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Figure b shows the FTIR spectra of pure electrospun PAA and PI nanofiber sheets. The peaks at 1779 cm −1 and 1727 cm −1 are attributed to the characteristic absorptions of imide carbonyls, and the peak at 1381 cm −1 is corresponded to the absorption of imide C‐N band, which indicates that the PAA is successfully converted into PI .…”
Section: Resultsmentioning
confidence: 99%
“…Figure b shows the FTIR spectra of pure electrospun PAA and PI nanofiber sheets. The peaks at 1779 cm −1 and 1727 cm −1 are attributed to the characteristic absorptions of imide carbonyls, and the peak at 1381 cm −1 is corresponded to the absorption of imide C‐N band, which indicates that the PAA is successfully converted into PI .…”
Section: Resultsmentioning
confidence: 99%
“…When the imidization temperature was above 330 1C, the disappearance of the peaks at 3038 cm À 1 (CONH, N-H), and 1707 cm À 1 (CQO), and the appearance of characteristic imide carbonyl peaks at 1770 cm À 1 (symmetric CQO stretching) and 1710 cm À 1 (asymmetric CQO stretching) demonstrated the complete imidization process (Fig. 1C) [10]. No difference between the FT-IR spectra of A-PI-NFB-330 and A-PI-NFB-450 indicated that no change happened to the PI molecules when increasing the imidization temperature till 450 1C.…”
Section: Resultsmentioning
confidence: 86%
“…The method of introducing polar groups into Additional Supporting Information may be found in the online version of this article. 34,35 Ma et al developed a series of polyimides deriving from aromatic dianhydrides and aliphatic diamines. For instance, with increasing fluorine content in the polyimide repeating unit, the moisture uptake decreased linearly, which was beneficial to stable dielectric property.…”
Section: Introductionmentioning
confidence: 99%